Organization of minors’ protection from destructive information environment: Russian federal cities case study - S. E. Titor (Цифровая социология)
The relevance of protecting minors from destructive information is quite high, since in the modern world technology has taken a leading position in human life, including children’s, replacing not only live communication, but also transferring a person’s entire life to the Internet space. The information environment affects the upbringing of children, as they spend a lot of time in global networks. Based on the meaning of international norms and national legislation, the protection of children from destructive information should be organized, including at the regional level. Features of Russian cities of federal significance can serve as a basis for a separate study of their experience in organizing the protection of minors from a destructive information environment. This study analyzes such work in Moscow, St. Petersburg, and Sevastopol. The article uses the comparative legal method, the method of analysis, the formal legal method, the sociological method, the method of generalization. Cities of federal significance have been studied from the standpoint of the criminalization of minors. The regional legislation governing the protection of minors from the destructive information environment has been studied. The law enforcement practice on improving the media literacy of minors, educational work, extracurricular work with children and adolescents is analyzed. In conclusion, findings about the features of ensuring the protection of minors from destructive information in Russian cities of federal significance are drawn.